Pattern of Motorbike Spoke wheel injuries in children presenting to the Accident and Emergency Department of a Tertiary care hospital (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the pattern of motorbike spoke wheel injuries in terms of severity and location in children presenting to the Accident and Emergency Department of our hospital.Methods: We conducted this descriptive study in Accident and Emergency Department Liaquat University Hospital Hyderabad from 23rd January 2018 to 23rd January 2021.All children with motorbike spoke wheel injuries fulfilling the inclusion criteria were enrolled in this study. The location and severity of injury was noted and classified as per Tscherne and Oestern classification from grade 0 to grade III.Results: The total number of children in our study were 150.The mean age was 8.4±7.1 years. Male children were 111(74%) and female 39(26%).Right foot was injured in 103(68.66%) and left in 47(31.33%).Grade II injury was documented in 56(37.33%), grade I in 44(29.33%), grade III in 27(18%) and grade 0 in 23(15.33%) children. Heel pad was the commonest area injured in 82(54.66%) children. Tendon ruptures were seen in 14(9.33%) children. Fractures were noted in 12(8%) children. Neurovascular injury was noted in 1(0.66%) child.Conclusion: Motorbike spoke wheel injury had variable pattern of tissue damage and fractures. Most of the children had major soft tissue loss. Heel pad was the commonest injured area. Calcaneus and phalanges fractures were the commonest.